Biodiversity Journal 2018
DOI: 10.31396/biodiv.jour.2018.9.3.255.270
|View full text |Cite
|
Sign up to set email alerts
|

Infralittoral molluscs from the Scilla cliff (Strait of Messina, Central Mediterranean)

Abstract: The mollusc taxocoenosis characterizing the photophilic zone of the Scilla cliff (Strait of Messina, Central Mediterranean) has been described on hard bottom samples from 6, 16 and 24 m depth. Seasonality has been evaluated by replicates carried out in autumn and spring. Overall, 229 benthic taxa have been recorded, 87 of which occurred in both seasons, while 109 were exclusively recorded in spring and 29 only in autumn. Specimen abundance also notably decreased from autumn to spring (1581 and 892 individuals,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…Regarding anthozoans, Vafidis et al [72] found 21 taxa belonging to the orders Actiniaria, Corallimorpharja, and Scleractinia in the northern Aegean Sea, while we reported 16 of them, which could be comparable considering the smaller area investigated by our study. Also for molluscs, our species list is comparable to the one realised by Giacobbe & Renda [73] for Capo D'Armi, Sicily. They reported 133 taxa, compared to 144 taxa found in our study.…”
Section: Discussionsupporting
confidence: 62%
“…Regarding anthozoans, Vafidis et al [72] found 21 taxa belonging to the orders Actiniaria, Corallimorpharja, and Scleractinia in the northern Aegean Sea, while we reported 16 of them, which could be comparable considering the smaller area investigated by our study. Also for molluscs, our species list is comparable to the one realised by Giacobbe & Renda [73] for Capo D'Armi, Sicily. They reported 133 taxa, compared to 144 taxa found in our study.…”
Section: Discussionsupporting
confidence: 62%